Microbial Abundance and Nutrient Concentration in Riverine and Coastal Waters of North-East Langkawi - Chui Wei, Bong; Choon Weng, Lee, (Malaysian Journal of Science (MJS), 2005)
We measured both biotic and abiotic variables at 19 stations along the three river systems and also off the Langgun Island in the North-East (NE) Langkawi region. Temperature ranged between 29.8-31.3Ã‚Â°C whereas salinity ranged between 22-32. pH was between 7.4 and 8.2 whereas redox potential ranged between -82 to -32. Dissolved oxygen (DO) concentration ranged between 120-280 Ã‚ÂµM. Both pH and DO concentration were lower upstream of the rivers. For inorganic nutrient concentrations; ammonium (NHÃ¢â€šâ€ž) ranged between 0.56-4.30 Ã‚ÂµM, nitrate (NOÃ¢â€šÆ’) between 0.31-1.46 Ã‚ÂµM, nitrite (NOÃ¢â€šâ€š) between 0.04-0.38 Ã‚ÂµM and silicate (SiOÃ¢â€šâ€ž) between 1.36-15.23 Ã‚ÂµM. Of the nitrogen species, NHÃ¢â€šâ€ž was dominant, making up to 79% of total dissolved inorganic nitrogen (mean=57%). Total suspended solids (TSS) in the water samples were high, ranging between 270 to 330 mg LÃ¢ÂÂ»Ã‚Â¹ whereas particulate organic matter (POM) constituted a very small component of TSS (<5%, 3.6-14.4 mg LÃ¢ÂÂ»Ã‚Â¹). For biotic variables, chlorophyll a (Chl a) concentration that represented the photoautotrophs present in the water, with the range of 1.49-8.24 Ã‚Âµg LÃ¢ÂÂ»Ã‚Â¹. Bacteria ranged between 1.5-5.3Ãƒâ€”10Ã¢ÂÂ¶ cells mLÃ¢ÂÂ»Ã‚Â¹ whereas phototrophic picoplankton and protists ranged between 1.7-4.3Ãƒâ€”10Ã¢ÂÂµ cells mLÃ¢ÂÂ»Ã‚Â¹ and 0.8-1.6Ãƒâ€”10Ã¢ÂÂ´ cells mLÃ¢ÂÂ»Ã‚Â¹, respectively. Marine bacteria cultured ranged from 4Ãƒâ€”10Ã‚Â² to 1.2Ãƒâ€”10Ã¢ÂÂµ cfu mLÃ¢ÂÂ»Ã‚Â¹. Although our limited sampling was inadequate to detect controlling factors for bacterial abundance, our study showed that bacteria could have caused the lower DO concentration in the rivers in NE Langkawi